OP62 What are the physical and psychological health effects of suicide bereavement on family members?: a qualitative study. (2nd September 2017) - Spillane, A; Larkin, C; Corcoran, P; Matvienko-Sikar, K; Arensman, E
Abstract : Background: Research indicates that experiencing the suicide of a relative can have a significant impact on family members' psychological health. However, research incorporating the impact of suicide bereavement on family members' physical health is sparse. Therefore, the aim of this study was to examine how family members have been physically and psychologically affected by a relative's suicide. Methods: This exploratory qualitative study is a follow-up to a larger case-control study, which examined the psychological, psychiatric and work-related factors associated with suicide in Ireland (SSIS-ACE, 2014–2017). Participants for the SSIS-ACE study were next-of-kin of persons who died by suicide or probable suicide, who were identified via coroner's records. All participants who completed the SSIS-ACE interview and who consented to further follow-up were invited by letter to take part in the current study. Semi-structured interviews, with the use of a topic guide were conducted with 18 relatives experiencing suicide bereavement. Eleven participants were female and seven were male; participant's ages ranged from 25–73 years. Duration of bereavement ranged from 15 to 37 months. Thematic analysis was used to analyse the data which was facilitated by the use of NVIVO 11 to organise the data. Results: Preliminary findings indicate the emergence of five themes in two main domains, psychological and physical outcomes. Psychological outcomes: For most participants, the suicide was viewed as a predominantly negative turning point in their lives, where the death forced them to confront a new reality without their loved one. Secondly, immediate emotional reactions, including shock, disbelief, guilt, anger and surprise were reported. Suffering from persistent mental health difficulties was a recurrent theme among bereaved relatives: difficulties included depression, anxiety, stress, posttraumatic stress disorder, suicidal thoughts and suicide attempts. Coping mechanisms, both positive and negative, utilised by suicide survivors emerged as the fourth theme. Physical outcomes: Immediate physical reactions, including nausea, breathlessness, palpitations, chest pains and losing consciousness were physical reactions reported. Some of these physical conditions did not improve in the months after the death but rather persisted and sometimes worsened over time. Conclusion: Family members bereaved by suicide are at risk of mental and physical health sequelae, while also being vulnerable to suicidal thoughts and suicide attempts. Participants were drawn from a small geographic area and the findings of this study may not be generalisable to other settings. From a policy perspective, this study highlights the importance of providing support services for this group following suicide bereavement.